Didactic-pedagogical challenges of technical Education: 21st century’s Professional Training - Amorós, Antonio
The purpose of this article is to offer the readers especially to the education professionals and to the trainers connected to various projects, the newest pedagogical-didactic trends and pedagogical practices around Project-Based Learning (PBL). Thus, promoting the “didactic transposition”, implicit in the work with the training projects, requires a whole process of didactic innovation, fundamental for what we could call Project Pedagogy.